Three Models of a Sandwich Beam: Bending, Buckling, and Free Vibrations - MAGNUCKI, Krzysztof; MAGNUCKA-BLANDZI, Ewa; WITTENBECK, Leszek (Engineering Transactions, 2022)
This paper is devoted to the analytical modelling of a sandwich beam. Three models of this beam are elaborated. Two nonlinear individual shear theories of deformation of a plane cross-sections are proposed. Based on Hamilton’s principle, two differential equations of motion for each model are obtained. The bending, buckling and free flexural vibration problems of the simply-supported sandwich beam considering these three models are studied. The results of these analytical investigations are presented in tables.